ANALYSIS OF AEROBIC ENDURANCE (VO2MAX) USING THE MFT TEST FOR ATHLETES OF DOJANG SPEED TAEKWONDO IN PELALAWAN DISTRICT, RIAU PROVINCE - Ramadan, Arief (Universitas Muhammadiyah Kuningan, 2024)
The purpose of this study was to determine the aerobic endurance (Vo2Max) of athletes of dojang Speed Taekwondo Pelalawan Regency, Riau Province, and to find out the coach's efforts to improve the aerobic endurance of taekwondo athletes. In this study, researchers used a type of research with a quantitative approach. The method used in this research is the survey method with data collection techniques in the form of aerobic endurance tests using the MTF test.) Samples used in this study were 10 teenage class athletes of the Pelalawan Regency taekwondo speed dojang. The sampling technique in this study used purposive sampling. Aerobic Endurance (Vo2Max) Speed Taekwondo Youth Athletes Pelalawan Regency Riau Province is known that 3 athletes (30%) are categorized as very less, 6 athletes (60%) are categorized as less, 1 athlete (10%) is categorized as moderate. Based on this information, it can be seen that the results of the MFT test of teenage athletes Dojang Speed Taekwondo Pelalawan Regency Riau Province are categorized as